Collaborative and inclusive process with the autism community: A case study in colombia about social robot design (2020)
Abstract One of the most promising areas in which social assistive robotics has been introduced is therapeutic intervention for children with autism spectrum disorders (CwASD). Even though there are promising results in therapeutic contexts, there is a lack of guidelines on how to select the appropriate robot and how to design and implement the child–robot interaction. The use of participatory design (PD) methods in the design of technology-based processes for CwASD is a recognition of the stakeholders as “experts” in their fields. This work explores the benefits brought by the use of PD methods in the design of a social robot, with a specific focus on their use in autism spectrum disorders therapies on the Colombian autism community. Based on what proved to be effective in our previous research, we implemented participatory methods for both the CwASD and the stakeholders. The process leverages the active role of participants using a focus group approach with parents and specialists, and scene cards, narrative and handmade generative methods with the children. To overcome some challenges of traditional PD processes, where not all community actors are considered, we included a Colombian community consisting of therapists, nurses, caregivers and parents. The proposed PD process provides an opportunity to learn from several community actors (and thus different cultural and social aspects of developing countries), improving traditional robot design methods. In this way, the findings are summarized through a set of guidelines regarding the design of a social robot-device suitable to be implemented for robot-assisted therapy for CwASD.